Transepithelial photorefractive keratectomy for the management of hyperopic regression after conductive keratoplasty - Meduri, Alessandro (BMJ Case Rep, 2021)
Several refractive techniques are available for the treatment of hyperopia. Conductive keratoplasty (CK) is a safe and non-ablative procedure suitable for the treatment of low hyperopia and presbyopia. Due to the high rate of regression, it is not a commonly used technique. There is minimal literature about the use of refractive procedures for the treatment of hyperopic regression after CK. We report a case of a 49-year-old man who had undergone bilateral CK 15 years before for the correction of his hyperopia. He experienced a regression, with sph +2.75 cyl −0.50(20) in the right eye and sph +2.50 cyl −0.75(170) in the left eye. Transepithelial photorefractive keratectomy (tPRK) was performed with Schwind Amaris 750 s. After 12 months, his best-corrected visual acuity was 20/20, with −0.25 sph in both eyes. To the best of our knowledge, this is the first reported case of tPRK performed after CK.